Penerimaan Sistem Informasi Akuntansi Pada Pusat Kesehatan Masyarakat Yang Baru Menjadi Badan Layanan Umum Daerah (BLUD) - Rudy Suryanto; Mohamad Abdul Latif; Hafiez Sofyani (Universitas Muhammadiyah Malang, 2017)
This study aims to analyze the acceptance of public service agency (BLUD) accounting information system at BLUD health center in Boyolali, Center Java. TAM model is used in this study with behavioral theory perspective that used to for examine information technology adopted process. The samples used in this research is accounting and financial staffs at BLUD health center in Java that using BLUD accounting information system that developed by PT. Syncore Indonesia. Data obtained from questionnaires distributed be procesed using partial least square (PLS).The result of this research indicated 8 of 11 hipotheses are accepted. Where the result of this research showed relationship between users abilities and skills (UAS) toward percieved ease of use (PEOU), accounting information system (SIA) toward percieved usefulness (PU), percieved ease of use (PEOU) toward percieved usefulness (PU), percieved ease of use (PEOU) and percieved usefulness (PU) toward attitude toward using (ATU), percieved usefulness (PU) and attitude toward using (ATU) toward behavioral intention to use (BITU), and behavioral intention to use (BITU) toward actual system usage (ASU) are positif significant. Keywords: Accounting Information System, Public Service Agency (BLUD), Structural Equation Model, Technology Acceptance Model (TAM)